2019
DOI: 10.1016/j.concog.2019.102764
|View full text |Cite
|
Sign up to set email alerts
|

Development of synaesthetic consistency: Repeated autonomous engagement with graphemes and colours leads to consistent associations

Abstract: Synaesthetic consistency is the hallmark of synaesthesia and plays an important role in the definition and validation of synaesthesia. It has been hypothesised that the acquisition of initially unspecified synaesthetic associations is based on consolidation processes. Thus, we investigated in non-synaesthetes whether repeatedly engaging with grapheme-colour associations mimics the developmental trajectory of synaesthetic consistency in genuine grapheme-colour synaesthesia. This was the case for the two tested … Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
5
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
6

Relationship

1
5

Authors

Journals

citations
Cited by 6 publications
(5 citation statements)
references
References 47 publications
0
5
0
Order By: Relevance
“…The associative nature of synaesthesia has led many to speculate that a learning component must be involved in the development of specific synaesthetic associations, especially when the inducers are cultural artefacts, as it is the case in grapheme-colour synaesthesia [5,6,10,43]. In line with this claim, the induced forms of synaesthesia reviewed here cast doubt on claims that genuine synaesthetic phenomenology can only occur in a rare subset of the population that exhibit a genetic predisposition [73,74].…”
Section: Discussionmentioning
confidence: 99%
See 3 more Smart Citations
“…The associative nature of synaesthesia has led many to speculate that a learning component must be involved in the development of specific synaesthetic associations, especially when the inducers are cultural artefacts, as it is the case in grapheme-colour synaesthesia [5,6,10,43]. In line with this claim, the induced forms of synaesthesia reviewed here cast doubt on claims that genuine synaesthetic phenomenology can only occur in a rare subset of the population that exhibit a genetic predisposition [73,74].…”
Section: Discussionmentioning
confidence: 99%
“…For this reason, it will be interesting to investigate in future studies whether training-induced synaesthesia is associated with cognitive benefits found in natural synaesthesia, such as an enhanced memory (for a review, see [2]). A first training study, which examined if grapheme-colour associations are based on the consolidation of environmental contingencies, provides preliminary evidence that this may be the case [43].…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…Studies with bilingual synesthetes revealed that synesthetic responses for the more recently obtained language depended upon similarity to the primary language (Mills et al, 2002, 2009; Mroczko et al, 2009; Rich et al, 2005; Witthoft & Winawer, 2006; also see Barnett et al, 2009 for review). Importantly, new grapheme-color associations can become highly consistent through repetition, even in adulthood (Ovalle-Fresa & Rothen, 2019). For example, Uno et al (2021) reported that as their adult subjects became increasingly familiar with rare Japanese characters over periods of 5 to 8 years, their grapheme-color synesthetic associations become more stable.…”
Section: Introductionmentioning
confidence: 99%